THE EFFECT OF POINT-COUNTERPOINT STRATEGY ON STUDENTS ‘ABILITY IN SPEAKING SKILL AT THE EIGHTH GRADE OF UPTD SMP NEGERI 1 GUNUNGSITOLI IN 2022/2023. - Donata Deli Bertin Gea; Adieli Laoli; Nursayani Maru’ao; Kristof Martin E Telaumbanua (Universitas Muhammadiyah Makassar, 2023)
This research aimed to investigate whether is there a significant effect of Point-Counterpoint Strategy on Students’ ability in Speaking Skill or not. The research was conducted by using Quantitative Research especially in Quasi-Experimental Design. The Population of the research was eighth grade of UPTD SMP Negeri 1 Gunungsitoli that consisted of 287 students. The research took sample which consist of 64 students by using Cluster Sampling Technique. The instrument used in collecting data was Directed Response Task. The instrument of my research is sound record, handphone, and documentation. The test was validated by three validators and it was stated valid. Then the researcher gave the pre-test and post-test to experimental class and control class to find the normality and homogeneity of the sample. After conducting the research, the researcher analyzed the data and the result shows (1) the mean score of students’ ability in pre-test of experimental class was 66,41 and control class was 61.10. (2) The mean score of students’ ability in post-test of experimental class 87,22 and in control class was 70.00. (3) The result of testing hypothesis , the researcher found that tcount was 12.127 and ttable was 1.659. Since tcount(12.127) ttable(1.659), it can be concluded that Ha is accepted. (4) There is a significant effect of Point-Counterpoint Strategy on students’ ability in speaking skill especially in expressing asking and giving opinion at the eighth grade of UPTD SMP Negeri 1 Gunungsitoli in 2022/2023.Furthermore, the researcher has some suggestion related to the research: (1) The English Teacher should use Point-Counterp oint Strategy in teaching Speaking especially in expressing asking and giving opinion material. (2) The English Teacher should be able to guide the students in practicing speaking orally by using expression, dialog, and enhancing the students’ vocabulary. The researcher suggest for the next researcher to use Point-Counterpoint Strategy in the other skill of language.